The Improving Reading Literacy through the GUIDED READING Learning Model of Indonesian Language Subjects in Elementary School Students - Putri Ameliana; Marlina Bakri; Muhammad Hasby (EDUJAVARE: International Journal of Educational Research, 2026)
The classroom action research conducted by this study aims to solve the problem of students' lack of reading literacy by using the guided reading learning model in grade II students at SDN 42 Limpomajang, Palopo City. The subjects of this study were 10 students with details of 5 male students and 5 female students. The data analysis technique used is quantitative descriptive. Based on the test results obtained by applying the guided reading learning model, it is proven to be able to increase students' reading literacy. This is proven to meet the success indicators, namely 90% of students or 9 out of 10 students get a score of ≥73 in accordance with the KKTP. In addition, student learning activities are classified as very active and the implementation of learning is also in the category of very implemented. Since the success indicators have been achieved in cycle I, the research is not continued to the next cycle. Thus, the implementation of the Gided Reading learning model was declared successful in improving students' reading literacy.